DANAU KEBUN NOPI DESA BUKIT PEDUSUNAN KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI SEBAGAI TEMPAT REKREASI KELUARGA - Winda Apriani; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
At present the condition of Nopi Garden Nopi is no longer good due to the damage to the embankment that collapsed on Lake Nopi Lake. So the minimum number of visitors who come to Nopi Garden Lake. Therefore the study aims to describe Lake Nopi Lake as a place for Family Recreation. This study uses descriptive qualitative methods. The subjects of this study were key informants, namely Nopi garden Lake Manager, Head of Destination for Culture and Tourism of Kuantan Singingi Regency, the Community around Nopi Garden Lake, and additional informants, namely Nopi Garden Lake Visitors.Data collection techniques used are observation, documentation, and interviews.The results showed that the Nopi Garden Rustic Hill Village Mudik Quantity District, Kuantan Singingi Regency as a place for family recreation was no longer functioning. For the attraction activities at Lake Nopi Garden, it is no longer good, as there are no more activities to play bicycle water, due to damage to Nopi Garden Lake. Facilities at Lake Nopi Garden are no longer good.Keyword:Attractions,Facilities,Nopi Garden Lake